The OMA orthology database in 2018: retrieving evolutionary relationships among all domains of life through richer web and programmatic interfaces. Issue Volume 46:Issue D1(2018) (2nd November 2017) - Altenhoff, Adrian M; Glover, Natasha M; Train, Clément-Marie; Kaleb, Klara; Warwick Vesztrocy, Alex; Dylus, David; de Farias, Tarcisio M; Zile, Karina; Stevenson, Charles; Long, Jiao; Redestig, Henning; Gonnet, Gaston H; et al.
Abstract: The Orthologous Matrix (OMA) is a leading resource to relate genes across many species from all of life. In this update paper, we review the recent algorithmic improvements in the OMA pipeline, describe increases in species coverage (particularly in plants and early-branching eukaryotes) and introduce several new features in the OMA web browser. Notable improvements include: (i) a scalable, interactive viewer for hierarchical orthologous groups; (ii) protein domain annotations and domain-based links between orthologous groups; (iii) functionality to retrieve phylogenetic marker genes for a subset of species of interest; (iv) a new synteny dot plot viewer; and (v) an overhaul of the programmatic access (REST API and semantic web), which will facilitate incorporation of OMA analyses in computational pipelines and integration with other bioinformatic resources. OMA can be freely accessed at https://omabrowser.org .